Three-in-one polyimide-based blended membrane for Upgrading helium separation performance and physical aging resistance - Bingbing Gao; Yiran Peng; Ming Wu; Hua Ma; Jianchao Sun; Peng Zhang; Xingzhong Cao; Like Ouyang; Xiaobin Fu; Chunfang Zhang; Yunxiang Bai; Lijun Liang; et al. (Advanced Membranes)
Polyimide membranes have attracted considerable attention for gas separation applications; however, achieving efficient helium (He) separation remains a significant challenge due to the low fractional free volume (FFV) and poorly controlled pore size distribution. Here, we report a novel three-in-one polyimide-based blended membrane constructed from a polymer (6FDA-TFMB) and alkynyl-based polyimide (EBPA-TB) matrix via thermal crosslinking. By carefully designing membrane synthesis and structure, the resulting membrane achieves the “1 ​+ ​1>2” effect: (i) high He selectivity derived from reinforced interphase adhesion and size-sieving ability due to the hydrogen bonding and similar structure between 6FDA-TFMB and EBPA-TB; (ii) high He permeability derived from the rigid cross-linked network distorting the EBPA-TB chain packing and generating additional free volume; (iii) high anti-aging performance derived from the thermal crosslinking preventing microstructural rearrangements. The optimal membrane an unprecedented combination of high He permeability (51.24 Barrer), excellent He/N2 selectivity (146.40) and remarkable aging resistance (less than 3.97 % of permeability decrease over 50 days), outperforming the performance of state-of-the-art polyimide-based blended membranes for He purification. This three-in-one blended membrane construction strategy provides a general toolbox for the development of next-generation, high-performance blended membranes with desirable performance for diverse industrial applications.